"Christianity, Commerce and Civilization": Child Labor and the Basel Mission in Colonial Ghana, 1855–1914. (18th November 2014) - Koonar, Catherine
Abstract Focusing specifically on colonial Ghana between 1855 and 1914, this article aims to situate the history of child labor in colonial Africa within the larger historiography of African labor history. Relying primarily on the records of the Basel Mission, this article complicates the narrative of labor history by studying how the mission acquired and sustained the labor of children and youth at various mission stations as part of the greater "missionary project." This article argues that childhood in colonial Ghana can be viewed as a site of contestation between the competing interests of patriarchy, race, and colonial and missionary authority, in which the labor of children was used to achieve a larger degree of control and influence in the region.